KARAKTERISASI RESERVOAR DAN PERHITUNGAN CADANGAN HIDROCARBON BERDASARKAN ANALISA PETROFISIKA PADA LAPANGAN âLEâ FORMASI TALANG AKAR CEKUNGAN JAWA BARAT UTARA - , FX. NICKOE SITUMORANG ([Yogyakarta] : Universitas Gadjah Mada, 2014)
A research on reservoir characterization based on petrophysical analysis and hydrocarbon reserve calculations have been done on âLEâ field, Talang Akar Formation, North West Java Basin, in the working area of PT. Pertamina EP Asset 3. Reservoir characterization based on petrophysical analysis is important to be done to get some of reservoir properties which are used for reserves calculation such as effective porosity, water saturation, net to gross, and permeability. In petrophysical analysis, shale volume calculated using Clavier non-linear method, effective porosity calculated using neutron/density Bateman-Konen method, water saturation calculated using Indonesia equation, and permeability using Coates FFI equation. Then, the prospect reservoirs are picked on seismic data to obtain the reservoirâs volume based on its geometry so the total oil reserves can be calculated using volumetric method with the petrophysical data and seismic interpretation result as parameter input. From the result analysis, there are prospect reservoir which have been calculated with porosity cut-off value 8%, Vshale cut-off value 40%, and water saturation cut-off value 70%. Those reservoirs are sand-1 reservoir with reserve value 3.827 MMbbl, sand-2 reservoir with reserve value 33.919 MMbbl, and sand-3 reservoir with reserve value 41.964 MMbbl. Key word : Petrophysical analysis, Seismic Interpretation, Reserves calculation.